2019
DOI: 10.1021/acsapm.9b00130
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-Functionalized Latex Polymers Display Improved Adhesion to Low-Surface-Energy Thermoplastic Polyolefin Substrates

Abstract: We report the synthesis and characterization of catechol-functionalized film-forming latexes that display excellent adhesion to low-surface-energy polyolefin-based substrates. The aromatic 1,2-diol functional group in catechol derivatives is believed to be responsible for enhancing the adhesion of a variety of polymers to a range of substrates. Here, we describe a postpolymerization modification approach to the design of emulsion polymers with catechol-functionalized side chains. A series of analogous small-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Furthermore, we speculate that unreacted phenolic OH or catechol groups that have not been modified by the aliphatic esters contribute to the high adhesion properties. Recently, it has been found that catechol groups covalently functionalize to the latex polymer, stimulating adhesion properties . Overall, it can be said that the pull-off adhesion strength of the lignin-based system is in the range of other commercially available polyester-melamine-based coatings (2-15MPa). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, we speculate that unreacted phenolic OH or catechol groups that have not been modified by the aliphatic esters contribute to the high adhesion properties. Recently, it has been found that catechol groups covalently functionalize to the latex polymer, stimulating adhesion properties . Overall, it can be said that the pull-off adhesion strength of the lignin-based system is in the range of other commercially available polyester-melamine-based coatings (2-15MPa). …”
Section: Resultsmentioning
confidence: 99%
“…Adhesion properties of 20 ± 5 μm thick coatings of steel surfaces were analyzed using a cross-cut tape test (ASTM D3359-97) and a pull-off test (ASTM D4541). 23,43,44 The cross-cut tape test was obtained with an Elcometer 1542 Cross Hatch tester equipped with a multiple-blade cutting wheel with a 1 mm separation. The adhesive tape was placed on the grids and then removed with a firm pulling action.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These works could be traced back to Messersmith et al’s publication for reversible wet/dry adhesives using catechol-containing poly­(acrylamide-acrylate)-coated nanofabricated polymer pillars . After that, the design of mussel-inspired polymers is under fast growth, and many polymers conjugated with catechol moieties have been reported. , Although both synthetic and natural polymers are used as the backbone for mussel-inspired polymers, the former are more widely studied due to their structural abundancy, including but not limited to synthetic polypeptides, , polyols, polystyrenes, polyacrylate/amides, , hyperbranched polymers, poly­(urethane-urea)­s, , polyvinyl alcohols, , and polyvinylpyrrolidones. , For example, Deming and Yu reported the synthesis of catechol containing copolypeptides via N -carboxyanhydride polymerization, which exhibited a tensile strength up to 4.0 MPa on aluminum . Becker et al reported the synthesis of amino-acid-based poly­(ester-urea) copolymers with pendant catechol groups via interfacial polycondensation, which exhibited a tensile strength up to 3.5 MPa on aluminum .…”
Section: Introductionmentioning
confidence: 99%